Artificial intelligence in Dentistry: Impact and perspectives in the management of dental clinics, a review of the literature (Research, Society and Development, 2024)
Introduction: Advances in artificial intelligence (AI) began in 1943 and the term was coined in 1956 by John McCarthy. In dentistry, physical AI includes sophisticated robots, while virtual AI operates through advanced software. AI-based virtual assistants improve clinical management and diagnostic accuracy by facilitating appointment scheduling, medical history collection, and alerting on critical patient data. AI complements the skills of dentists, promoting personalized care and efficiency in digital processes to raise the quality of dental care. Methodology: The methodology used the PICO approach to study clinical applications of AI in dentistry. An exhaustive search was carried out in databases such as Pubmed, Google Scholar and Elsevier, selecting articles published in the last 10 years. Results: AI applications are both physical and virtual. These AI tools reduce errors, improve accuracy, and optimize patient tracking. Therefore, it can be added as a complement to dentists by allowing greater precision, better patient experience and better results. Conclusion: This review highlights the great potential of AI to transform dental clinic management and improve the quality of dental care, provided that ethical and privacy challenges are adequately addressed. This literature review aims to provide updated information on the current impact and future prospects of artificial intelligence in dentistry, highlighting its potential to transform dental clinic management and improve the quality of dental care.